2015
DOI: 10.1080/10590501.2015.1096882
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pyrrole-Protein Adducts—A Biomarker of Pyrrolizidine Alkaloid-Induced Liver Injury in Humans

Abstract: Pyrrolizidine alkaloids (PAs) induce liver injury (PA-ILI) and is very likely to contribute significantly to drug-induced liver injury (DILI). In this study we used a newly developed ultra-high performance liquid chromatography-triple quadrupole-mass spectrometry (UHPLC-MS)-based method to detect and quantitate blood pyrrole-protein adducts in DILI patients. Among the 46 suspected DILI patients, 15 were identified as PA-ILI by the identification of PA-containing herbs exposed. Blood pyrrole-protein adducts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 41 publications
(20 reference statements)
5
61
0
1
Order By: Relevance
“…The findings indicated that serum PPAs had a diagnostic sensitivity of 100.0%, a specificity of 94.1%, a positive predictive value of 95.8%, and a negative predictive value of 100.0%. Blood PPAs assayed by ultra‐high‐performance liquid chromatography‐triple quadrupole‐mass spectrometry can serve as a specific biomarker of PA‐induced liver injury . High serum PPA concentrations indicate a poor prognosis, but few hospitals are equipped able to perform this assay.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that serum PPAs had a diagnostic sensitivity of 100.0%, a specificity of 94.1%, a positive predictive value of 95.8%, and a negative predictive value of 100.0%. Blood PPAs assayed by ultra‐high‐performance liquid chromatography‐triple quadrupole‐mass spectrometry can serve as a specific biomarker of PA‐induced liver injury . High serum PPA concentrations indicate a poor prognosis, but few hospitals are equipped able to perform this assay.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…Blood PPAs assayed by ultra-high-performance liquid chromatography-triple quadrupole-mass spectrometry can serve as a specific biomarker of PA-induced liver injury. 59 High serum PPA concentrations indicate a poor prognosis, but few hospitals are equipped able to perform this assay.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…In this specific study, the observed HSOS were confirmed to arise from the consumption of a PA-containing plant, Gynura segetum (L.) DC. Another study with PA-induced liver injury led to the conclusion that pyrrole-protein adducts were present in the blood of all the patients, further strengthening the case for their use as biomarkers for this kind of liver injury [ 55 ].…”
Section: Toxicitymentioning
confidence: 99%
“…Herbal dietary supplements and other herbal products have been recognized as the common causes of drug-induced liver injury. [96] A recent report indicates that dietary/herbal supplements are implicated in 19% of drug-induced acute liver failure cases, [97] because consumers often purchase these products online without the supervision of a health care provider and are not aware of drug-herb interactions and appropriate warnings. A total of 1179 English-language, herbal product- related websites (including retail and nonretail websites) were examined and only ~10% of them recommended consultation with a health care professional.…”
Section: Perspectivesmentioning
confidence: 99%